Examining virtual visit use during a pandemic and perspectives of primary care providers, patients and caregivers: a mixed-methods research protocol. Issue 8 (5th August 2022) - Halas, Gayle; Singer, Alexander; Katz, Alan; Labine, Lisa; Baldwin, Alanna; Wong, Sabrina T; Kirby, Sarah; Bohm, Eric; Abrams, Elissa; MacKay, Kerri; Francois, Jose; Talpade, Siddhesh
Abstract : Introduction: COVID-19 prompted rapid shifts to virtual primary care; however, the secondary implications and ideal applications of this change require further consideration. Patient and public stakeholder input has been bypassed. To integrate virtual care (VC) in what currently appears to be a lengthier battle against COVID-19 and related sequelae, further investigation is needed to support ideal implementation and use. This study aims to describe factors associated with the use of virtual visits in primary care practices, along with more in-depth description of users' experiences and perspectives. Methods and analysis: This study will be conducted in three phases, using a mixed-methods approach and in consultation with community advisors. Phase 1 will analyse data from electronic medical records (EMRs) to characterise the use and users of VC in primary care during the early phase of the COVID-19 pandemic. Analysis will be primarily descriptive; regression modelling will assess associations between patient and provider factors with a virtual visit. In phase 2, we will use an EMR-facilitated process to automate the distribution of patient surveys within an estimated 10 clinics. These surveys aim to describe care experiences, transactional use and perspectives of VC. In phase 3, focus groups with patients, caregivers and primary care clinicians will seek more in-depth exploration of VC regarding accessibility of care, acceptability and perceptions of quality care. Interpretive phenomenological analysis will be used for thematic analysis. The framework method will employ a matrix structure to organise the data and to facilitate comparison, integration and further interpretation. Ethics and dissemination: This study has been approved by the University of Manitoba's Health Research Ethics Board (HS24197). A co-designed dissemination strategy will include reports and infographics to policymakers and the public, manuscripts and presentations to academic and clinician audiences, and contributions to a learning plan for professional development.